Family-, media-, and school-related risk factors of video game addiction: a 5-year longitudinal study - Rehbein, Florian (Journal of media psychology, 2013)
In recent years, a variety of epidemiological studies have provided empirical data on the prevalence of video game addiction (GA) in different age groups. However, few studies investigated the causes of GA and could explain why video game playing as a widespread phenomenon leads to a comparatively small percentage of addicted players. Additionally, the existing longitudinal studies mainly consider psychological trait variables and neglect the possible explanatory value of predictors in socialization regarding media availability, media use, and family and everyday school life. In this paper, the results of a two-wave longitudinal study comprising a sample of students from Grades 4 to 9 (N = 406) are presented. The data show that 15-year-old video game addicts had already exhibited a number of specific risk factors at the age of 10. Students from single-parent families seem to be particularly at risk, as are students with low experienced school well-being and with a weaker social integration in class. The data also indicate that problematic use of video games in childhood increases the risk of GA in adolescence. Male students are especially vulnerable for developing GA. The results of this study are an important contribution to understanding risk factors for GA in adolescents, thereby laying the groundwork for effective prevention measures.